569 LAPAROSCOPIC REPAIR OF A VOLUMINOUS SYMPTOMATIC HIATAL HERNIA USING AN ABSORBABLE SYNTHETIC MESH. (14th September 2020) - Cocozza, E; Berselli, M; Livraghi, L; Quintodei, V; Latham, L
Abstract:  : In symptomatic voluminous paraesophageal hiatal hernias not only a laparoscopic surgical approach, but also the use of mesh can be considered too. The use of surgical protesis in hiatal henia repair was a debated surgical topic in the last years A laparoscopic repair of a symptomatic type III hiatal hernia by plastic of the hiatus, fundoplicatio and use of an absorbable glycolic acid/trimethylene carbonate synthetic mesh is showed. Methods: The patient was a 59 years old male suffering from recurrent aspiration pneumonias. Surgery was performed by a standardized tecnique in a high volume laparoscopic surgical centre. The hernia sac was removed and the plastic of the esophageal hiatus was performed. After the mesh placement a Nissen fundoplicatio was performed. No drain was placed. Results: In the postoperative period a contrat-soluble swallow was performed and it resulted in a good transit witout any sign of recurrence. The patient was discharged with an appropiate oral intake. One year after surgery the patient is asymptomatic and in good conditions. Conclusion: A voluminous symptomatic hiatal hernia can be successfully treated in a high-volume and long-term experienced laparoscopic surgical. The use of an absorbable, handily positionable and synthetic mesh can help to gain a lower rate of recurrence without any risk for the patients. The technical skill and all the surgical steps never are renounceable because of the presence of the mesh. Further studies with a longer-term follow-up and a international live debate are necessary. Video: https://www.dropbox.com/s/384ujzm3rnoqe0a/Hiatal%20Hernia%20Dr.%20Cocozza%20ISDE%202020.mp4?dl=0